The Application Research of Randomized Network Coding in ForCES Router - Ming Gao; ShiJu Li; Bangzhi Xiao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
ForCES router(ForTER) is an open experimental platform for network research of new routing algorithm，packet processing which is based on ForCES. By introducing and designing six new LFBs to ForTER, this paper propose a method of implementation of multicast IP router with network coding enabled. These LFBs undertake coding functions such as packets’ coding, labeling, buffering and decoding. We build an IP multicast network with ForTERs, which including the classic shortest path tree constructed by the reverse path from the source node to each sink ,then evaluate the completeness of throughput , performance overhead and CPU utilization. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2005